(3ebGdI Ydi QSGdI GdOMQLIs - (3eMehO Hf eSYhO Hf eUdM GdaGQSj GdYdGej , bWH GdOjf , GdbWH GdTjQGRj,J (B710 (3g` s ((3egQGH Hf CejQ MGL s)
(3ChdgG (B:s
(3hHYO MeO Gddg Ydi fYeGFg GdeJhGaQI jbhd GdTjQGRiWdYJ ai MQcI GdOMQLI hai GdfSHI ef GdeSJhi hGdefMfi s
(3BNQgG (B:s
(3dGjecf EUdGMg HERGdI Jdc GdMGdGJ hOaY Jdc GdTHgGJ aEf GdNWC GdebJQf HGdbeQ hGdLRA GdeYQha GdEOQGc EOQGc hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG HYV GdCTcGd GdgfOSjIs
(3QSGdI GdOMQLI gi LRA ef fgGjI GdEOQGc TQMgG CMO GdYdeGA hbQCg GdTjQGRi aYed Ydjg JbQjQkG HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B187 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B20 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B407s
Keywords: (3Gdadcs